The institution of impeachment in the Ukrainian legal order - Domańska, Aldona (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The legal and political position of the head of state of Ukraine is determined by the scope of his/her responsibility. Pursuant to the provisions of the Constitution the President of the Republic of Ukraine may be removed from office under the procedure of impeachment. This article is devoted to this very issue. The aim of the conducted research is to present the specifics of the Ukrainian impeachment institution. This is to be achieved primarily by the legal-dogmatic method. It will allow not only to carry out a reliable exegesis of norms, but also to confront the views of representatives of Polish and Ukrainian doctrine on the subject under study.